Investigating a human DNA repair helicase that supports CRISPR editing - Cubbon, Andrew (2022)
In the last decade, CRISPR-associated proteins such as Cas9 and Cas12a have become powerful gene-editing tools for research, with great potential for therapeutic applications. However, barriers remain to their successful implementation, one of which is understanding the interaction of these systems with DNA repair processes. Previous research has identified HelQ, an ATP-dependent single-stranded DNA helicase implicated in replication-coupled repair, as a major factor in the efficient integration of template DNA through homology-directed pathways. HelQ has also been identified as a prognostic biomarker for several different cancers and a promising target in platinum-resistant ovarian tumours. We hypothesised that HelQ removes Cas-proteins from the sites of double-strand breaks, but in vitro assays utilising both synthetic DNA substrates and supercoiled plasmid DNA were unable to confirm this. Alongside this, a system of human-derived cell-free extracts was reconstituted to study the impact of individual DNA repair proteins on integration efficiency. Further exploration into the role of HelQ in the resolution of DNA:RNA hybrids was also undertaken, ultimately finding conflicting evidence for the participation of the protein. Previous research has demonstrated sensitisation to DNA-crosslinking agents in HelQ-deficient cells. To further characterise the importance of this, research was conducted using HelQ-depleted cell lines. This generated preliminary data laying the groundwork for a future functional genomic screen against HelQ. Finally, using fragment-based drug discovery techniques, a small molecule screen identified putative inhibitors against HelQ in vitro. Subsequent testing to validate and characterise hits identifying several candidates with micromolar IC50 values. Experiments to determine the mode-of-action suggest that many compounds were competitive with ATP, although several candidates were identified which may disrupt HelQ DNA binding or helicase activities.